The cv. rocha pear tree - Faoro, Ivan Dagoberto (2019)
This article presents and discusses the agronomic characteristics, rootstocks, pollinator cultivars, harvest and storage of the cv. Rocha plant. This pear tree originates from Portugal and is currently cultivated in colder regions of Brazil, especially the Southern. Its fruits range from small to medium-size, have a pyriform shape and excellent quality for in natura consumption. The fruit has high resistance to handling and a good period of post-harvest storage, but this cultivar is susceptible to Fabraea leaf spot and scab.